He Awa Whiria: Braiding Social and Emotional Learning with Bicultural and Intentional Teaching - Julie Houghton-Katipa (New Zealand Journal of Teachers' Work)
This article explores the intersection of three crucial constructs in early learning: social and emotional learning, bicultural practice, and intentional teaching. It considers the potential advantages of integrating these constructs to enhance children's learning experiences and shape future teaching practices. It emphasises the importance of the first five years of a child's life in their social and emotional development and recognises the significant influence of kaiako in this process. While prioritising social and emotional learning, there is a need to support teachers in articulating their evidence-based practices. Despite recognising the importance of social and emotional learning within Māori contexts, there is a gap in understanding how kaiako integrate bicultural practices into supporting social and emotional learning. Intentional teaching, a cornerstone in early learning, is strongly evident in the refreshed Te Whāriki 2017, along with an enhanced bicultural framing. Drawing from a larger research study, this article presents an overview of existing key research and suggests a potential way forward for kaiako to intentionally support social and emotional learning through drawing on the richness of the Māori language, culture and traditions, realising the bicultural aspirations of Te Whāriki (Ministry of Education, 2017).